Correlation of Thyroid Stimulating Hormone (TSH), T3, and T4 Hormones with Histopathological Characteristics of Thyroid Cancer at Cipto Mangunkusumo General Hospital - Kurnia, Ahmad; Bangun, Kristaninta; Muazdhani, Fatahillah (The New Ropanasuri Journal of Surgery, 2023)
Introduction. In a study spanning 2008 to 2012 at Cipto Mangunkusumo General Hospital (CMGH) Jakarta, 668 cases of thyroid cancer were identified among 18,216 cancer cases. Globally, the papillary subtype is prevalent, and prior research indicates a link between thyroid hormone changes and thyroid carcinoma risk. To improve surgical care, this study aims to find the association between thyroid hormone levels and histological subtypes in thyroid carcinoma patients. Method. This cross-sectional study focused on thyroid cancer patients managed from 2013 to 2017. Despite subjects' characteristics, thyroid hormone levels and histopathological findings were the variables of interest. The findings were analyzed using ANOVA, Kruskal-Wallis, unpaired T-tests, Mann-Whitney tests, and Pearson or Spearman tests to find correlations with age, gender, clinical presentation, and body mass index. Results. The mean age was 48.7 years, with subjects having an average body weight of 64.5 kg, height of 154.4 cm, and BMI of 24.8 kg/m2. Hormonal analysis revealed mean T3 levels at 2.02 ng/mL, T4 levels were slightly lower at 1.92 ng/mL, and TSH levels were the lowest at 1.22 ng/mL. A very weak correlation existed between the T3 hormone and age (r = 0.05, p = 0.77). In the correlation between T4 thyroid hormone levels and age, a weak correlation was found between T4 thyroid hormone levels and age (r = 0.31, p = 0.08). In the correlation between thyroid cancer histopathology and gender, clinical presentation, and BMI, there was no significant association with gender, ?s = 0,01; 95% ??? [-3,37; 3.34]; p=0,94 Conclusion. This study indicates that the TSH, T3, and T4 hormone levels were not associated with the histopathological characteristics of thyroid cancer at CMGH. The T3, T4, and TSH hormone levels were unaffected by gender, nodule involvement, and age